Psychosocial Risk Factors and Work Stress among Hospital Healthcare Workers - Wikan Rizky Atmaja; Maria Goretti Catur Yuantari; Slamet Isworo (Edusight International Journal of Multidisciplinary Studies, 2026)
Work stress among hospital healthcare workers is a significant occupational health issue  that affects psychological well-being and healthcare service quality. Hospital work environments are characterized by high job demands, time pressure, emotional responsibilities, and complex organizational systems that increase exposure to psychosocial risks. This study aimed to analyze psychosocial risk factors associated with work stress among hospital healthcare workers. A systematic literature review using a PRISMA-based approach was conducted by analyzing 28 primary research articles published between 2019 and 2024 retrieved from PubMed, Scopus, ScienceDirect, and Google Scholar. The findings indicate that high workload, time pressure, role conflict, role ambiguity, and low organizational support are the most consistent psychosocial risk factors contributing to increased work stress. In contrast, social and organizational support, adaptive coping strategies, and individual resilience function as protective factors that reduce stress levels. These findings highlight that work stress among hospital healthcare workers is primarily shaped by the interaction between job demands and job resources as described in the Job Demands–Resources model. Therefore, organizational-level psychosocial risk management strategies, including workload regulation, supportive leadership, and strengthening institutional support systems, are essential to improve healthcare workers’ psychological well-being and maintain hospital service quality.